A Simplified Method to Predict the Crush Behavior of Offshore Bonded Rubber Hose - Pan Gao; Chuangchuang Li; Hui Wang; Qiang Gao; Youan Li (Journal of Marine Science and Engineering, 2023)
Crush load is one of the common loads for offshore composite rubber hoses. It may induce the damage of the hose on the reel and the tanker reel hose. A theoretical approach is proposed to evaluate the response of the hose to the crush load, which is fulfilled in three steps. (1) The hose wall is treated as a composite shell, and its mechanical properties are deduced based on the rule of the mixture of the composite. (2) The composite hose is equalized as a homogeneous hose, and the equivalent shell thickness is determined based on the strain energy equivalence. On one hand, the relationship between the strain energy and the wall thickness is theoretically deduced for the equivalent homogeneous hose. On the other hand, an FE model of the composite hose is loaded to obtain the strain energy. The equivalence of the two models implies the equality of the strain energy. Therefore, the strain energy is used to calculate the wall thickness of the equivalent homogeneous hose. (3) The response of the homogeneous hose to the crush load is deduced based on the elastic shell theory. The proposed method is validated against an indoor test. It is found that the proposed approach slightly overestimates the rigidity of the hose. This is probably due to the initial imperfection of the test specimen, which reduces the rigidity of the hose. The proposed approach could be a valuable tool for the future design of offshore composite rubber hoses.